Synaptic pathology in the cerebellar dentate nucleus in chronic multiple sclerosis - Albert, Monika (Brain Pathol, 2017)
In multiple sclerosis, cerebellar symptoms are associated with clinical impairment and an increased likelihood of progressive course. Cortical atrophy and synaptic dysfunction play a prominent role in cerebellar pathology and although the dentate nucleus is a predilection site for lesion development, structural synaptic changes in this region remain largely unexplored. Moreover, the mechanisms leading to synaptic dysfunction have not yet been investigated at an ultrastructural level in multiple sclerosis. Here, we report on synaptic changes of dentate nuclei in post‐mortem cerebella of 16 multiple sclerosis patients and eight controls at the histological level as well as an electron microscopy evaluation of afferent synapses of the cerebellar dentate and pontine nuclei of one multiple sclerosis patient and one control. We found a significant reduction of afferent dentate synapses in multiple sclerosis, irrespective of the presence of demyelination, and a close relationship between glial processes and dentate synapses. Ultrastructurally, we show autophagosomes containing degradation products of synaptic vesicles within dendrites, residual bodies within intact‐appearing axons and free postsynaptic densities opposed to astrocytic appendages. Our study demonstrates loss of dentate afferent synapses and provides, for the first time, ultrastructural evidence pointing towards neuron‐autonomous and neuroglia‐mediated mechanisms of synaptic degradation in chronic multiple sclerosis.